Implementasi Desain Pembelajaran Inovatif Ppda Masa Pandemi Covid-19 di SDN Pondok Jengkol - Magdalena, Ina; Septiani, Amalia; Rafidah, Aura Rahmatun (TSAQOFAH, 2023)
Schools in Indonesia have stopped offering in-person instruction due to the spread of the Covid-19 pandemic. Instead, students learn through online or distance learning. For online and distance education, qualified and easily accessible technology support is required. Revolution 4.0 is the right learning program that can be used today to respond to technological advancements and educational advancements. However, Indonesia's human resource issues, particularly those pertaining to schoolchildren, remain extremely complex. When it comes to teaching, teachers also face a lot of challenges. As a result, the purpose of this community service project, which takes the form of online-based learning design training during the Covid-19 pandemic, is to boost teachers' ability to implement online-based learning designs at Pondok Jengkol Public Elementary School in Tangerang. This service uses mentoring and training to plan and create online learning designs. Participants in this service activity will be able to create online learning designs by incorporating technology into public elementary school education. The improvement of online-based learning plans is bundled as logical articles, then, at that point, a collection of internet learning plans is made. The book can be used as a reference to add scientific knowledge and insights to public elementary school learning about online-based learning design.